Torsional Stresses of Composite Fiberglass at High Shear Strain Rate - Abbas Abdulla, Fadhel; Adnan Khalaf, Waad (International Journal of Engineering and Technology, 2018)
Using Torsional-Split-Hopkinson-Bar (TSHB),the dynamic behavior of pure epoxy that reinforced with random (shape) fiberE glass using five twistedangles (4 ÌŠ, 6 ÌŠ, 8 ÌŠ, 10 ÌŠ and 12 ÌŠ) was investigated experimentally. The fiber used in this work was Threads of fiber (140 mmlength).A new clamp system mechanism is used in this work.Using three volume fraction (55, 40 and 25%), the composites samples were prepared. The results show that, the increasing shear strain rate for all types of these samples causes increasing in maximum shear stress, and shear strain. At angles of twist Ó¨=12 ÌŠ, when the volume fraction increased from 25% to 40% , the shear strain, shear strain rate and shear stress are increased by 12.4%, 18.9%, and 12.5%respectively, as well when the volume fraction increased from 40% to 50% , the shear strain, shear strain rate and shear stress increased by 8.7%, 6.4%, and 5.5% respectively. The shear stress and shear strain for fiber E glass- epoxy composite sample at 55 volume fractionand 594 stain rate are 61 Mpa and 5.1 respectively.Â